2014
DOI: 10.1080/10668926.2014.882805
|View full text |Cite
|
Sign up to set email alerts
|

The New Reverse Transfer: A National Landscape

Abstract: For decades, higher education professionals and researchers have used the term reverse transfer to describe a specific group of students. A current review of community college literature and higher education policy reflects a contextual change of the term, and today reverse transfer has grown to include students who transfer from a two-year college to a four-year institution and retroactively receive an associate's degree with their newly earned university credits. The purpose of this study was to provide an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 5 publications
0
38
0
Order By: Relevance
“…However, transfer pathways between two and fouryear institutions are complicated: only 24% of community college students who indicated a desire to transfer actually enroll in a four-year institution six years later (National Center for Education Statistics, 2011). In addition, research has found patterns of lateral transfers (Bahr, 2009), reverse transfers (Friedel & Wilson, 2015;Winter & Harris, 1999), and co-enrollment (Wang & Wickersham, 2014) between two and four-year institutions creating a student swirl among community colleges and universities. Given this complexity, some researchers have called for call for alternative classifications of higher education institutions not just by the type of credentials awarded but through a more multifaceted approach related to program and student characteristics (Skolnik, 2011).…”
Section: Coercive Isomorphismmentioning
confidence: 99%
“…However, transfer pathways between two and fouryear institutions are complicated: only 24% of community college students who indicated a desire to transfer actually enroll in a four-year institution six years later (National Center for Education Statistics, 2011). In addition, research has found patterns of lateral transfers (Bahr, 2009), reverse transfers (Friedel & Wilson, 2015;Winter & Harris, 1999), and co-enrollment (Wang & Wickersham, 2014) between two and four-year institutions creating a student swirl among community colleges and universities. Given this complexity, some researchers have called for call for alternative classifications of higher education institutions not just by the type of credentials awarded but through a more multifaceted approach related to program and student characteristics (Skolnik, 2011).…”
Section: Coercive Isomorphismmentioning
confidence: 99%
“…Although this type of reverse transfer will not be the focus of this study, it is important to include all versions of reverse transfer. New reverse transfer emerged around 2006, partially in response to the college completion agenda, and can be defined as "the transferring of credit from a four-year college back to a two-year college to retroactively earn an associate's degree" (Friedel & Wilson, 2015). The new reverse transfer students transfer from a two-year institution to a four-year school prior to completing an associate's degree, and then transfer credits from the baccalaureate institution back to the two-year college to be applied toward the completion of an associate's degree.…”
Section: Newmentioning
confidence: 99%
“…Agreements for new reverse transfer policies and practices among two-year and four-year institutions have been implemented on both institutional and statewide levels as a way to increase completion rates at community colleges. The concept of reverse transfer in this scenario refers to the transfer of the credit not the individual (Friedel & Wilson, 2015).…”
Section: Newmentioning
confidence: 99%
“…The reverse transfer credit agreement has been increasingly looked at as one opportunity to increase degree completion numbers. The new reverse transfer is defined as students who transfer from a two-year college to a four-year institution and retroactively receive an associate's degree with their newly earned four-year college credits (Friedel & Wilson, 2015). As the implementation of the new reverse transfer program has been revamped in higher education institutions across the U.S., many students have participated and received their associate's degree through this program.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…This research could contribute to the literature by providing additional insight into the influence students perceive they have received by obtaining a degree through the new reverse transfer program. New reverse transfer students are defined as those who transfer from a two-year college to a four-year institution and retroactively receive an associate's degree with their newly earned four-year college credits (Friedel & Wilson, 2015). This qualitative study focused on new reverse transfer completers who attended Iowa State University (ISU) within the last five years (2012-2016) who then left ISU without completing their bachelor's year degree.…”
Section: Purpose Of the Studymentioning
confidence: 99%